203k views
11 votes
I know the answers but my calculations won't provide them and i need to know what work to show

the answers are
a) x^2+7x+10
b) x^2-x-6

I know the answers but my calculations won't provide them and i need to know what-example-1

2 Answers

8 votes

Step-by-step simplification:

≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡

1a) (x + 2)(x + 5)

⇒ (x × x) + (5 × x) + (2 × x) + (2 × 5)

⇒ (x²) + (5x) + (2x) + (10)

⇒ (x²) + (5 + 2)x + (10)

(x²) + (7)x + (10)

≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡

1b) (x + 2)(x - 3)

⇒ (x × x) + (-3 × x) + (2 × x) + (2 × -3)

⇒ (x²) + (-3x) + (2x) + (-6)

⇒ (x²) + (-3 + 2)x + (-6)

x² + (-1)x - 6 = x² - x - 6

≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡

User DomaNitro
by
4.9k points
3 votes


a)\\\\(x+2)(x+5)\\\\=x(x+5) + 2(x+5)\\\\=x^2+5x+2x+10\\\\=x^2+7x+10\\\\\\b)\\\\(x+2)(x-3)\\\\=x(x-3)+2(x-3)\\\\=x^2-3x+2x-6\\\\=x^2-x-6

User David Brown
by
4.9k points